Analysis of the Implementation of the General National Safety Plan (RUNK) Policy on National Road Traffic in East Java Province - Dwi S. N. Yunita; Anak A. G Kartika (Institut Teknologi Sepuluh Nopember (ITS), 2026)
This study analyzes the implementation of the National Road Safety General Plan (RUNK) in East Java Province, Indonesia, and its effectiveness in reducing road traffic accidents and fatalities. Despite the national framework, East Java consistently records one of the highest accident rates in the country. The research evaluates the application of the five RUNK pillars—road safety management, safer roads, safer vehicles, safer road users, and post-crash response—using secondary data from 2010 to 2023, including accident frequencies, fatality counts, vehicle ownership, and population statistics. Quantitative methods such as accident rate (AR) and case fatality rate (CFR) analyses, along with comparative statistical tests (t-test and Mann–Whitney), were employed to assess regional performance disparities and policy consistency across districts. The findings reveal that the implementation of RUNK remains inconsistent, particularly in Pillars 3 and 5, contributing to the failure in achieving national targets. This study contributes to the UN Sustainable Development Goals (SDGs), especially SDG 3.6 by providing evidence to support the reduction of road traffic deaths and injuries, and it also aligns with SDG 11.2, SDG 9.1, and SDG 16.6 through recommendations for safer transport systems, improved road infrastructure, and stronger inter-agency governance. The study highlights the need for stronger inter-agency coordination, improved road safety infrastructure, and enhanced public education to effectively address road safety challenges at the regional level.